Africa s need for soil management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Sustainable Agriculture in Sub Saharan Africa. The role of soil productivity By A J Rayar, 2000. ISBN 81 7525 181 6 $US 35 Euro 41.55